2004
DOI: 10.1007/s00296-003-0323-2
|View full text |Cite
|
Sign up to set email alerts
|

Anemia, serum vitamin B12, and folic acid in patients with rheumatoid arthritis, psoriatic arthritis, and systemic lupus erythematosus

Abstract: The incidences of anemia and decreased serum B12 levels were high in these three groups of rheumatic patients. However, true tissue deficiency seems to be much rarer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 20 publications
0
30
0
2
Order By: Relevance
“…Although the relation between CLYBL and the vitamin B12 serum levels remains unclear, a link between vitamin B12 and RA has been described. In a report by Regal et al , 24% of RA patients had low vitamin B12 serum levels and 26% of them had true vitamin B12 deficiency 31. Besides, a previous study described that RA patients with vitamin B12 deficiency, folate deficiency, vitamin B6 deficiency and impaired renal function showed associated hyperhomocysteinemia that may have a role in promoting high cardiovascular morbidity in patients with RA 32.…”
Section: Discussionmentioning
confidence: 95%
“…Although the relation between CLYBL and the vitamin B12 serum levels remains unclear, a link between vitamin B12 and RA has been described. In a report by Regal et al , 24% of RA patients had low vitamin B12 serum levels and 26% of them had true vitamin B12 deficiency 31. Besides, a previous study described that RA patients with vitamin B12 deficiency, folate deficiency, vitamin B6 deficiency and impaired renal function showed associated hyperhomocysteinemia that may have a role in promoting high cardiovascular morbidity in patients with RA 32.…”
Section: Discussionmentioning
confidence: 95%
“…Vitamin B12 deficiency associated with psoriasis has been reported 31, 32 . A retrospective observational study of 98 patients with plaque psoriasis and 98 healthy controls demonstrated lower vitamin B12 levels in psoriasis patients compared to healthy controls 31 .…”
Section: Resultsmentioning
confidence: 99%
“…Zur An ä mieinzidenz bei anderen entz ü ndlichen Gelenkerkrankungen gibt es deutlich weniger Untersuchungen. Segal et al wiesen bei 46 % ihrer ambulanten Patienten mit Psoriasisarthritis eine An ä mie nach, was nahezu der H ä ufi gkeit bei den untersuchten RA-Patienten (49 % ) entsprach [30] . In einem Kollektiv mit ankylosierender Spondylitis (AS) trat eine An ä mie bei M ä nnern mit < 10 % deutlich seltener auf, w ä hrend Frauen mit AS in etwa einem Drittel der F ä lle an ä misch waren [20] .…”
Section: Zusammenfassungunclassified